2018
DOI: 10.1590/0102-672020180001e1370
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Meld Score (Model for End-Stage Liver Disease) and Derivatives in Cardiac Transplantation

Abstract: Introduction: Heart transplantation is still the best therapeutic alternative for the treatment of end-stage heart failure. The use of criteria that consider the complications associated with this procedure can guarantee a better evaluation of the recipient and prepare the team for possible unsatisfactory post-transplant results. The use of the MELD score has been expanded to evaluate cirrhotic patients undergoing various procedures, including cardiac transplantation. Objective: To analyze the knowledge on ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…They argued that a high MELD-XI score was an independent predictor of cardiac death and all-cause death in patients with HF. In addition, Moraes[ 11 ] suggested that the use of MELD could contribute to the evaluation of the severity of HF in patients who are candidates for transplantation. This could help in setting up a system, similar to liver transplantation, of priority-based transplants for patients requiring a transplant at the earliest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that a high MELD-XI score was an independent predictor of cardiac death and all-cause death in patients with HF. In addition, Moraes[ 11 ] suggested that the use of MELD could contribute to the evaluation of the severity of HF in patients who are candidates for transplantation. This could help in setting up a system, similar to liver transplantation, of priority-based transplants for patients requiring a transplant at the earliest.…”
Section: Discussionmentioning
confidence: 99%
“…This could help in setting up a system, similar to liver transplantation, of priority-based transplants for patients requiring a transplant at the earliest. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca, antikoagülan kullanımı nedeniyle hesaplama sırasında INR'yi hariç tutan modifiye MELD skoru olan MELD-XI'nun çeşitli kardiyavasküler girişim sonuçlarını tahmin etmede yararlı olduğu doğrulanmıştır (10,11). Ek olarak, INR yerine albümin serum değerini içeren MELD-Albumin skorunun kalp nakli ve çeşitli kalp kapağı girişimi sonrası klinik sonuçlarla ilişkili olduğu gösterilmiştir (12,13). Bununla birlikte, primer perkütan koroner girişim (pPKG) uygulanan STEMI hastalarında bu 2 modifiye MELD skoru daha önce çalışılmamıştır.…”
Section: Introductionunclassified
“…This is a mathematical model that estimates the mortality risk of a patient with terminal liver disease based on the following laboratory tests: total bilirubin, creatinine and INR 13 . This model was previously developed to predict the survival of cirrhosis patients subjected to transjugular intrahepatic portasystemic shunt (TIPS), since some studies have proven that it could be used as a reliable tool to evaluate survival in patients with chronic liver disease 10 , 14 . In general, MELD presents two important advantages in the search for better hepatic allocation.…”
Section: Introductionmentioning
confidence: 99%